RESEARCH OF FACTORS AFFECTING THE CROSS-BORDER RMB INVESTMENT AND FINANCING - Qian, Zhang (European Scientific Journal, ESJ, 2014)
The operation of cross-border settlement with RMB was in full swingsince 2011. the cross-border RMB investment and financing projectsincreased gradually, it is of practical and important significance for theinternationalization of RMB. Based on the theoretical analysis of the factorsthat may influence the cross-border RMB investment and financing, and theexisting literature, we choose the gross domestic product (GDP) and theRMB exchange rate as main variables, and make an empirical analysis of thecross-border RMB investment and financing with the PARCH model. Theresults show that the stability of RMB‘s value has a relatively large impacton the cross-border RMB investment and financing. And then, werecommend the relevant policies.